Adherence to physical activity guidelines among cancer support group participants. (15th October 2013) - Stevinson, C.; Lydon, A.; Amir, Z.
<x xml:space="preserve">Abstract</x> Physical activity is recommended after cancer diagnosis for physical function, quality of life and survival benefits. This study provided preliminary data on the prevalence of physical activity among adult men and women with cancer in the UK. As part of a national survey of cancer support group participation, questionnaires including items on leisure‐time physical activity and demographic information were completed by 748 cancer survivors. Overall, 395 (52.8%) participants reported no weekly moderate or vigorous intensity physical activity, 221 (29.5%) reported some activity but below minimum recommendations and 132 (17.6%) were meeting published guidelines. Gender, health status and socio‐economic status were independently associated with meeting guidelines. Among participants in good or fair health who were not meeting guidelines, 59.9% thought that they ought to be more physically active. In conclusion, overall levels of physical activity are low among cancer survivors in the UK. However, the majority of insufficiently active participants showed awareness of the need to increase their activity, and may be receptive to interventions for promoting physical activity in this population.